Microbial antimonate reduction and removal potentials in river sediments. (March 2021) - Yang, Ziran; Hosokawa, Hisaaki; Kuroda, Masashi; Inoue, Daisuke; Ike, Michihiko
Abstract: Antimony (Sb), a toxic metalloid, exists mainly as Sb(V) and Sb(III) in the aquatic environment. Sb(V) displays greater solubility and can be reduced to insoluble Sb(III) compounds by microbial activities under anaerobic conditions, thus affecting the environmental fate of Sb. This study was conducted to evaluate the potential of Sb(V) reduction and removal from the aqueous phase by microbial communities existing in river sediments with and without the impact of Sb mining activities. Among the 14 tested sediment samples, which were collected from an urban river without Sb impact and a river flowing through mining area, microbial communities in two samples could reduce and remove Sb(V) in the presence of high concentrations of sulfate, whereas those in other six samples could reduce Sb(V) even under low sulfate concentrations, indicating the relatively wide distribution of microbial Sb(V) reduction potential in the environment, irrespective of the anthropogenic impact. The Sb(V) reduction and removal abilities under different sulfate levels also suggested the presence of multiple types of Sb(V) reduction and removal pathways, including the direct Sb(V) reduction by anaerobic respiration, indirect (chemical) Sb(V) reduction by sulfide produced by microbial sulfate reduction, and their combination. Furthermore, analysis of microbial communities in two enrichment cultures, which were constructed from sediment samples with Sb(V) reduction ability under the minimum sulfate condition and maintained Sb(V) removal ability during 28-d enrichment process, revealed possible contribution of several microbial taxa such as Azospira, Chlostridium, Dechloromonas, Dendrosporobacter, and Halodesulfovibrio to Sb(V) reduction in sediment microbial communities. Highlights: Sb(V) reduction and removal potential of microbial communities was evaluated. Microbial Sb(V) reduction potential was widespread, irrespective of Sb exposure. Sb(V) reduction occurred irrespective of the sulfate level. Sb(V) reduction and removal were likely to occur through various pathways. Several microbial taxa possibly contributing to Sb(V) reduction were identified.